English Language Assessment Testing: Key Strategies for Indian Students - Suneetha, Dr.Y.; Andoju, Srinivas.; P, KousaruBasha . (The journal of contemporary issues in business and government, 2020)
Proficiency in English language is the need of the hour in the present day scenario. It is not sufficient to have a simple degree to get into higher studies or achieve good placement in a reputed MNCs. English language Tests have grown in importance in the aspects study and work overseas. These tests determine the level of proficiency for non-native speakers, and provide a means to compare fluency among individuals. English language exams can be divided into three categories: Academic, Business and General. Academic English Exams include IELTS, STEP, APTISand TOEFL generally demonstrate the levels of English proficiency.Business English language exams like the TOEIC and BULATS are internationally recognized credentials required by the employers for the level of English in the workplace. General English language exams like the CPE, FCE, KET are used to demonstrate a level of English mastery. This paper studies the significance of the current English language Testing system, preparation strategies and score bands by shedding the light on the plight of Indian students. It widely discusses the strategies of international boards like Cambridge, British Council and available resources including Apps. The study conducts simple survey on the engineering students who have taken STEP Exam. The findings are presented with an analysis of the performance of Indian students by providing the suitable suggestions. Further, it makes a comparative analysis of these different tests and provides clarity for the aspirants.